Pengaruh Citra Merek Dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Smartphone Iphone (Studi Kasus Pada Mahasiswa UPI) - Fajar; Yulasmi; Dodi Suryadi (CV. ITTC INDONESIA, 2024)
This research aims to determine and attempt to analyze the influence of brand image and product quality on customer loyalty with customer satisfaction as an intervening variable on iPhone smartphones (case study of UPI students). This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are UPI